Symptomatic bone marrow metastases in breast cancer: A retrospective cohort study - Yang, Ruohan; Jia, Lin; Lu, Guanyu; Lv, Zheng; Cui, Jiuwei (Frontiers in Oncology, 2022)
Objective: Breast cancer bone marrow metastasis (BMM) is rare with poor prognosis. Chemotherapy is usually the primary treatment with limited efficacy. Dose reduction and decrease in quality of life due to the adverse effects of the agent. In addition to chemotherapy, there is a lack of other treatment studies for BMM. The purpose of this study was to explore the clinicopathological characteristics of BMM patients with breast cancer, the prognosis using different treatment modalities, and the risk factors that affect the prognosis. Methods: This retrospectively study included patients who were diagnosed with breast cancer BMM from January 2018 to January 2022 in the Cancer Center of the First Hospital of Jilin University. The analysis focused on the characteristics of the patients, the treatment regimen, and prognosis. Results: Of 733 patients with advanced breast cancer, thirty-three patients were identified with BMM. All patients showed hemoglobin decrease, 25 (75.75%) presented with fever of unknown origin. As for metastasis breast cancer subtype, 25 (75.75%) had hormone receptor(HR) positive, Human Epidermal Growth Factor Receptor 2 (HER-2) negative, 3(9.09%) HER-2 overexpression and 5 (15.15%) triple negative. The BMM patients had median progression free survival (mPFS) of 7 months (1-21 months) , median overall survival (mOS) of 18 months (2-108 months). Among 25 HR +, HER-2 - BMM patients treated with different modalities, the mOS of endocrine therapy(ET) group was 23 months, while 5 months in the chemotherapy group. Cox proportional hazards models suggested that higher Easten Coorerative Oncology Group (ECOG) scores and old age were associated with shorter survival. Conclusion: When breast cancer patients present with anemia and fever with negative etiological test, especially for the patients with bone metastases, BMM should be considered. For HR+, HER2 - patients with good physical status and can receive active treatment, CDK4/6 inhibitors combine with AI can be used to control disease progression, improve quality of life, and prolong survival.